PEMANFAATAN TEKNOLOGI DIGITAL DALAM MICRO TEACHING UNTUK MENINGKATKAN KETERAMPILAN MENGAJAR PJOK - Neza Sembiring, Boy; Gratama Purba, Febrindo; Marselo Surbakti, Rendi; Gonzales Nainggolan, Rahul; Endriani, Dewi; Ardilla, Rafika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital technology enhances the quality of microteaching and the teaching competencies of prospective teachers through the use of media such as videos, online platforms, and interactive devices, including in Physical Education (PJOK) instruction, which impacts students’ understanding, motivation, and engagement. However, specific studies on the integration of digital technology in Physical Education microteaching remain limited, particularly those that comprehensively address cognitive, affective, and psychomotor aspects, and they still face challenges related to infrastructure, digital literacy, and curriculum. This study aims to examine the utilization of digital technology in Physical Education microteaching through a literature review to analyze concepts, impacts, effectiveness, and challenges as a foundation for developing 21st-century learning models.